143 Identification of human thrombus formation in a translational model of deep arterial injury. (June 2018) - Andrews, Jack; Wilson, Simon; Lucatelli, Christophe; Walton, Tashfeen; MacNaught, Gillian; Alcaide, Carlos Corral; Tavares, Adriana; Dweck, Marc; Newby, David
Abstract : Background: Identification of in vivo thrombus formation has the potential to assist in the diagnosis and management of acute coronary atherothrombosis. ENC2015 is a 13-amino acid fluorescent peptide analogue of 2-antiplasmin which binds to newly formed thrombus. Our aim was to assess the binding of both optical (Cy5) and PET (18F) labelled ENC2015 acute human thrombus formation in a translational model of deep arterial injury. Methods: In healthy volunteers, blood was drawn through 3 ex-vivo perfusion chambers maintained at 37°C. Each chamber contained a denuded strip of porcine aorta as a model of deep arterial injury. In the optical study each subject participated in three sequential runs; Sequence 1 – ENC2015 +blood; Sequence 2- ENC2015 +inhibitor (iodoacetamide) +blood; Sequence 3 – blood only. In the PET study, each participant participated in only sequence 1 and 2. All sequences can be seen in figure 1. Optical Results Macroscopic fluorescence of high shear thrombi in sequence 1 was significantly greater than sequence 2 (C.I −25.47 to −3.45, p=0.016; figure 2, graph C) and 3 (C.I −28.9 to 4.41, p=0.018; figure 2, graph C). Microscopic fluorescence of sequence 1 was greater than sequence 2 in both high shear thrombi (C.I −1862 to −1358, p=0.0001; figure 2, graph A) and low shear thrombi (C.I −4782 to −3236, p=0.0001; figure 2, graph B). Microscopic fluorescence in sequence 1 was greater than 3 in both high shear (CI −2138 to −1638, p=0.0001; figure 2, graph A) and low shear thrombi (C.I −5008 to −3398, p=0.0001; figure 2, graph B). Fluorescence of sequence 1 was also greater than ENC2015 without blood (no thrombus) as well as a factor XIII control agent and a free Cy5 unbound to ENC2015. PET Results Thrombus uptake (KBq/cc) of 18F-ENC2015 was on average 16.93 times greater in low shear thrombi in sequence 1 compared to sequence two. In the first group of high shear thrombi 18F-ENC2015 uptake was on average 9.27 times greater in sequence 1 than sequence 2. Similarly, group 2 high shear thrombi uptake in sequence 1 was on average 5 times greater than sequence 2 (figure 2, graph D). Conclusion: Providing real-time characterisation of in vivo human coronary thrombus formation is vital for our appreciation of the pathophysiology of unstable coronary plaque events. We have demonstrated that our optical and PET probe rapidly binds to acutely formed human thrombus in an environment simulated to that of diseased human coronary arteries.